English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-04-30 01:11:56 · 3 answers · asked by maya820 1 in Science & Mathematics Mathematics

3 answers

Do you mean -2x² + 7x + 3 ? Because +7x+3x is just 10x.

D = b² – 4ac
D = 7² - 4*(-2)*(3)
D = 49 - 4*(-6)
D = 49 + 24
I hope you can do the rest of it.

2007-04-30 01:18:47 · answer #1 · answered by morningfoxnorth 6 · 0 0

The discriminant is b^2 - 4ac, where the quadratic expression is rewritten as ax^2 + bx + c.

I initially misread this as -2x^2 + 7x + 3, and I got b^2 - 4ac = 7^2 - 4(-2)3 = 49 + 24 = 73. But if your original text is correct, it can be rewritten as -2x^2 + 10x, and the result is b^2 - 4ac = 10^2 - 4(-2)0 = 100 - 0 = 100.

2007-04-30 08:16:16 · answer #2 · answered by DavidK93 7 · 0 0

= -2x^2+ 10 x
discriminate = 10^2 -4*(-2)* 0 = 100) (b^2-4ac)

2007-04-30 08:16:23 · answer #3 · answered by Mein Hoon Na 7 · 0 1

fedest.com, questions and answers